The evaluation of anxiety and panic agarophobia scores in patients with benign paroxysmal positional vertigo on initial presentation and at the follow-up visit. (4th May 2017) - Kahraman, Serif Samil; Arli, Cengiz; Copoglu, Umit Sertan; Kokacya, Mehmet Hanifi; Colak, Sait
Abstract: Conclusion: Patients with BPPV experienced short but intense anxiety and/or panic disorder, especially at the initial visit, but most patients recovered without medication with successful treatment. Objective: Recent studies have shown that people with dizziness report some psychological problems such as panic and agoraphobia and anxiety. The aim of this study was to evaluate anxiety and panic agorophobia levels in patients with benign paroxysmal positional vertigo on initial presentation and at the follow-up visit and compare the scores with the control group. Methods: All the 32 patients in the study had a diagnosis of BPPV confirmed by their history, typical subjective symptom reports, and characteristic positional nystagmus during the Dix–Hallpike test and/or Roll test. The patients were instructed to complete the standard forms of Beck anxiety inventory and panic agoraphobia scale questionnaire before and at 7 and 14 days after the canalith repositioning treatment. Results: The validity scores of panic agoraphobia were statistically significantly higher in patients with BPPV than in the control group in each period ( p < .001) and the validity scores of the Beck anxiety inventory were statistically significantly higher in patients with BPPV than in the control group at the first and second evaluation ( p < .001).